2003
DOI: 10.1111/j.1365-2605.2003.00434.x
|View full text |Cite
|
Sign up to set email alerts
|

Leptin and leptin receptor in human seminal plasma and in human spermatozoa

Abstract: Leptin, a 167 amino acid peptide, is known to influence the gonads via direct and indirect effects. Recent studies provide contradictory proposition about the peripheral impact of leptin in the male gonads. Thus, we examined leptin and its receptors in human seminal plasma and in human ejaculated spermatozoa by Western blot technique and fluorescence microscopy. In seminal plasma we found a free leptin band (16 kDa) by an anti-leptin polyclonal antibody. Incubation of seminal plasma with recombinant leptin cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
69
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(80 citation statements)
references
References 35 publications
4
69
0
2
Order By: Relevance
“…Jope et al (6) illustrated the presence of a leptin receptor on intact sperm plasma membrane, suggesting that it might have an impact on the gonadal function indirectly by the central neuroendocrine system and directly through the peripheral tissue membrane receptors. Ishikawa et al (24) showed that spermatogenic dysfunction is associated with increased leptin and leptin receptor expression in the testis.…”
Section: Discussionmentioning
confidence: 98%
“…Jope et al (6) illustrated the presence of a leptin receptor on intact sperm plasma membrane, suggesting that it might have an impact on the gonadal function indirectly by the central neuroendocrine system and directly through the peripheral tissue membrane receptors. Ishikawa et al (24) showed that spermatogenic dysfunction is associated with increased leptin and leptin receptor expression in the testis.…”
Section: Discussionmentioning
confidence: 98%
“…However new findings suggest that some of these transcripts can code for proteins essential in early embryo development [10]. Moreover, recent studies have shown that mRNA of leptin receptor is in human, swine and bovine spermatozoa [14,16,17]. However, to our knowledge, this is the first time that the presence of mRNA of Ob-R and Ob-Rb in ram epididymal spermatozoa has been demonstrated.…”
Section: Discussionmentioning
confidence: 69%
“…Because both epididymis regions express leptin and OBR at gene and protein levels, we could assume that this hormone may have a potential action on this organ in both spermatozoa and epithelial membrane. As leptin role on spermatozoa is still contradictory (Jope et al, 2003;Li, Chiu et al, 2009;LangeConsiglio et al, 2014) and we do not have enough information about its role on epididymis, further studies are necessary to establish in which epididymis functions leptin are involved.…”
Section: Discussionmentioning
confidence: 93%